Students' Perspectives Using Multimodal Approach in Language Teaching - Nursanti, Rachmi Retno; Azizah, Hilma Azmi (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study aimed to analyze students’ perception using multimodal in language teaching. The use of multimodal, such as video, audio, picture, power point, and digital resources in language teaching, particularly in English language, is beneficial to improve students’ understanding in acquiring target language. The outcomes of this study were revealed by the analysis of mixed-method research design. 36 students of the Geography Education Study Program revealed that more than 38,9% students were engaged and motivated, 44,4% students contributed learning effectiveness and comprehension, 36,1% students were able to develop English skills and preferences, and 41,7% students were getting easy access to the materials. Nevertheless, this study needed improvement to develop deepens learning needs in applying multimodal in English class. Furthermore, this study has implication to lecturers, teachers, and educators to increase students’ awareness and engagement in learning foreign language and bahasa Indonesia by utilizing multimodal approach.